Features of video information processing in differential correlator of pilotless flying machine - V. P. Gerasimov; A. Ju. Darzhanija; V. D. Kovalyov (Вестник Северо-Кавказского федерального университета)
The article provides a description of building and modeling an algorithm employed by an onboard videovisir controller in a pilotless vehicle (PV), which allows automatic detection and control of the fire focus in order to get the parameters describing the expansion dynamics.